Improvement of dielectric loss of (Ba,Sr)(Ti,Zr)O-3 ferroelectrics for tunable devices - Ha, Jong-Yoon; Choi, Ji-Won; Kang, Chong-Yun; Kim, Jin-Sang; Yoon, Seok-Jin; Choi, Doo Jin; Kim, Hyun-Jai (ELSEVIER SCI LTD, 2007)
(Ba0.6Sr0.4)(Ti1-xZr,)O-3 (0.05 <= x <= 0.3) ferroelectric materials have cubic perovskite structure and show paraelectric properties at room temperature. Curie point shifted to a negative value as increasing Zr content in (Ba0.6Sr0.4)(Ti1-xZrx)O-3 system. When Zr substituted 0.1 mol, the dielectric constant, dielectric loss, tunability, Curie point and FOM were 4500, 0.0005, 63%, -1.6 degrees C and 1260, respectively. This composition shows excellent microwave dielectric properties than those of (Ba0.6Sr0.4)TiO3 ferroelectrics, which are limelight materials for tunable devices such as varactors, phase shifters and frequency agile filters, etc. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: CERAMICS